Dependence disorders as disorders of society, family and individual: A critique of non-action - Dragišić-Labaš Slađana; Milić Milan (Sociologija, 2007)
Since early 1990s substance abuse and dependence among young people in our country has been growing. Therefore to devise a prevention program should be a task number one for the government. Social factors (economic and political crisis, forced migration, unemployment, etc), on one side, family disfunction and individual causes on the other, can result in insecurity fear, feeling of meaninglessness in the young mind and hence the need to "solve" these problems by using one of psychoactive substances (PAS). Studies have shown that the young and especially their families have a very poor knowledge of PAS - their kinds and uses, how to recognize a person (ab)using PAS, and what somatic and psychological consequences are produced by taking them. Social tolerance to alcohol use and abuse is high, society is supportive of alcohol use, while on the other hand individuals with substance dependence disorder are stigmatized and ostracized. The very first steps have been made in investigating this problem, some action has been taken, but serious comprehension of the problem and creation and realization of the national prevention program for substance use disorder are still missing.